A COMPARATIVE STUDY OF INVESTMENT IN ESG AND ANTI ESG FUNDS (IITM Journal of Business Studies, 2025)
In the realm of investment, Environmental,  Social, and Governance (ESG) criteria  have gained prominence as critical factors  influencing investment decisions. ESG focused funds invest in companies that  demonstrate strong practices in environmental  sustainability, social responsibility, and sound  governance. Conversely, Anti-ESG funds may  invest in companies that do not prioritize  or align with these principles. The research  process here involves a Literature Review and  Data Collection on ESG investing and Anti ESG strategies, followed by the Selection  of Investment Portfolios for a well-rounded  analysis. Secondly, there is a Performance  Analysis of the portfolios, Risk Assessment,  and Stakeholder opinion. Further, Statistical  Analysis and Sensitivity Analysis are used  to draw meaningful Conclusions and  Recommendations for investors.
Keywords: ESG funds; Anti-ESG funds; Long Term Value Creation; Risk Management; Risk Return Optimization; Sensitivity Analysis